2018
DOI: 10.1021/acs.chemmater.8b01385
|View full text |Cite
|
Sign up to set email alerts
|

Lead Bismuth Oxyhalides PbBiO2X (X = Cl, Br) as Visible-Light-Responsive Photocatalysts for Water Oxidation: Role of Lone-Pair Electrons in Valence Band Engineering

Abstract: We show that layered oxyhalides PbBiO2X (X = Cl, Br, I) with a Sillén-type structure possess band levels appropriate for visible-light-induced water splitting. Under visible light, PbBiO2Cl and PbBiO2Br with band gap (BG) of 2.51 and 2.48 eV, respectively, stably oxidized water to O2 in the presence of an Fe3+ electron acceptor. A comparison with structurally related SrBiO2Cl and BaBiO2Cl (BG = 3.55 and 3.54 eV) combined with DFT calculations revealed a significant interaction between O 2p and Pb 6s orbitals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
125
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(129 citation statements)
references
References 54 publications
4
125
0
Order By: Relevance
“…The band gaps were estimated to be approximately 3.0 eV for the X=F, Cl and Br materials and 2.7 eV for the X=I sample. It has been reported that the band gaps of SrBiO 2 X and PbBiO 2 X (X=Cl, Br, I) are reduced as the atomic number of X is increased. This effect is attributed to the ability of less electronegative X atoms to form valence bands at more negative potentials, as typically found in mixed anion compounds such as oxynitrides and oxysulfides .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The band gaps were estimated to be approximately 3.0 eV for the X=F, Cl and Br materials and 2.7 eV for the X=I sample. It has been reported that the band gaps of SrBiO 2 X and PbBiO 2 X (X=Cl, Br, I) are reduced as the atomic number of X is increased. This effect is attributed to the ability of less electronegative X atoms to form valence bands at more negative potentials, as typically found in mixed anion compounds such as oxynitrides and oxysulfides .…”
Section: Resultsmentioning
confidence: 99%
“…Oxyhalides have been studied as heterogeneous photocatalysts for pollutant decomposition and water splitting . Of particular interest is the development of visible‐light‐responsive photocatalysts that can utilize a wide range of the solar spectrum.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations